Breakthrough SARS–CoV‐2 Infections in Patients With Immune‐Mediated Disease Undergoing B Cell–Depleting Therapy: A Retrospective Cohort Analysis. Issue 12 (31st October 2022) - Calabrese, Cassandra M.; Kirchner, Elizabeth; Husni, Elaine M.; Moss, Brandon P.; Fernandez, Anthony P.; Jin, Yuxuan; Calabrese, Leonard H.
Abstract : Objective: Patients with immune‐mediated inflammatory diseases (IMIDs) receiving B cell–depleting therapy (BCDT) are among the most vulnerable to severe COVID‐19, as well as the most likely to suboptimally respond to SARS–CoV‐2 vaccines. However, little is known about the frequency or severity of breakthrough infection in this population. We retrospectively analyzed a large group of vaccinated IMID patients undergoing BCDT in order to identify breakthrough COVID‐19 infections and assess their outcomes. Methods: In this retrospective cohort study, the pharmacy records and COVID‐19 registry at the Cleveland Clinic were searched using specific International Statistical Classification of Diseases and Related Health Problems, Tenth Revision codes to identify IMIDs patients who 1) received treatment with BCDT, 2) were vaccinated against SARS–CoV‐2, and 3) experienced breakthrough infections. Each electronic medical record was reviewed to extract clinical data and outcomes. Univariate and multivariable logistic/proportional odds regression models were used to examine the risk factors for severe outcomes. Results: Of 1, 696 IMID patients receiving BCDT, 74 developed breakthrough COVID‐19 prior to December 16, 2021. Outcomes were severe, with 29 patients hospitalized (39.2%), 11 patients requiring critical care (14.9%), and 6 deaths (8.1%). Outpatient anti–SARS–CoV‐2 monoclonal antibodies were used to treat 21 patients, with 1 hospitalization and no deaths. A comparator analysis examining 1, 437 unvaccinated IMID patients receiving BCDT over the same time period identified 57 COVID‐19 cases (4.0%), with 28 requiring hospitalization (49.1%), including 7 deaths (12.3%). Conclusion: IMID patients receiving BCDT regardless of vaccine status appear to be vulnerable to infection with SARS–CoV‐2, and use of BCDT is frequently associated with severe outcomes. Outpatient use of anti–SARS–CoV‐2 monoclonal antibody therapy appears to be associated with enhanced clinical outcomes.